Managing risks in drug discovery: reproducibility of published findings - Kannt, Aimo; Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2016)
In spite of tremendous advances in biopharmaceutical science and technology, the productivity of pharmaceutical research and development has been steadily declining over the last decades. The reasons for this decline are manifold and range from improved standard of care that is more and more difficult to top to inappropriate management of technical and translational risks along the R&D value chain. In this short review, major types of risks in biopharmaceutical R&D and means to address them will be described. A special focus will be on a risk, i.e., the lack of reproducibility of published information, that has so far not been fully appreciated and systematically analyzed. Measures to improve reproducibility and trust in published information will be discussed.
Gesehen am 08.04.2019